Integrating Mahara Eportfolio in the Curriculum of English Language Teacher Education Study Programme - Reimannová, Irena (Centrum pro studium vysokého školství, 2018)
Portfolio, as a tool of professional autonomous development, plays an important role in the college training of not only student teachers, but also other future professionals. Based on the principles of social constructivism and reflective approach applied in student teacher training programmes, it represents a unique collection evidencing the process and outcomes of learning. Moreover, it may also provide wide opportunities to form and evaluate components facilitating students’ professional development for tutors (university teachers), involved in teacher training programmes. To integrate it meaningfully and appropriately into the curriculum of English Language Teacher Education study programme (including bachelor degree – English for Education) of the University of Pardubice (Department of English and American Studies), the eportfolio format, namely Mahara, was selected as it reflects in its technological perspective the above mentioned theoretical framework enriched with a technological dimension. As the process of eportfolio integration is gradual and longitudinal and has not started in the full extent yet, in the paper, only the initial phases of the process are described and further implications suggested. The paper focuses on the analysis and evaluation of the formal curriculum of the programme (aims and expected outcomes of the selected subjects from all the disciplines; approaches, methods and techniques used to support autonomous learning and self-reflective processes in those subjects and disciplines) and suggests possible ways of integrating Mahara into the curriculum.
Integrování eportfolia Mahara do kurikula studijního programu učitelství anglického jazyka
Keywords: eportfolio; Mahara; aims and outcomes; learning; student teacher training programme; eportfolio; Mahara; cíle a výstupy; učení; přípravné vzdělávání učitelů